Rapid adaptation to high temperatures in Chironomus riparius. Issue 24 (3rd December 2018) - Foucault, Quentin; Wieser, Andreas; Waldvogel, Ann‐Marie; Feldmeyer, Barbara; Pfenninger, Markus
Abstract: Effects of seasonal or daily temperature variation on fitness and physiology of ectothermic organisms and their ways to cope with such variations have been widely studied. However, the way multivoltines organisms cope with temperature variations from one generation to the next is still not well understood. The aim of this study was to investigate whether the multivoltine midge Chironomus riparius Meigen (1803) responds mainly via acclimation as predicted by current theories or whether rapid genetic adaptation is involved. To investigate this issue, a common garden approach has been applied. A mix of larvae from five European populations was raised in the laboratory at three different pre‐exposure temperatures (PET): 14, 20, and 26°C. After three and five generations, respectively, larvae were exposed to three treatment temperatures (TT): 14, 20, and 26°C. Mortality was monitored for the first 48 hr and after emergence. After three generations, significant mortality rate differences depended on an interaction of PET and TT. This finding supports the hypothesis that chironomids respond rapidly to climatic variation via adaptive mechanisms and to a lesser extent via phenotypic plasticity. The result of the experiment indicates that three generations were sufficient to adapt to warm temperature, decreasing the mortality rate, highlighting the potential for chironomids to rapidly respond to seasonally changing conditions. Abstract : In this manuscript, we investigated the way Chironomus riparius copes with temperature variations occurring in between generations. We used a common garden approach where we submitted C. riparius individuals at different temperatures after raising previous generations at constant temperatures and used mortality as response factor. The results were dependent not only to the treatment temperature but also on the temperature previous generations were raised at. This led to the conclusion that adaptation to temperature has occurred.